Oncidium ornithorhynchum, una especie mal interpretada y un nombre para una vieja especie: Oncidium sotoanum (Orchidaceae) - Jiménez Machorro, Rolando; Hágsater, Eric (Lankesteriana: International Journal on Orchidology, 2013)
The true identity of Oncidium ornithorhynchum Kunth is identified based on the type found at the Paris herbarium (P). It does not correspond to the well known Mexican and Central American species, but to O. pyramidale Lindl. from Ecuador, Colombia and Peru. The Mexican and Central American species is proposed as new: O. sotoanum R.Jiménez & Hágsater, and a new sub-species is also proposed, O. sotoanum ssp. papalosmum R.Jiménez, known only from the states of Oaxaca and Chiapas, Mexico.